2010
DOI: 10.1007/s10439-010-9945-1
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Validation of a New Method to Assess Aortic Pulse Wave Velocity from a Single Recording of a Brachial Artery Waveform with an Occluding Cuff

Abstract: Recently a new method has been proposed as a tool to measure arterial pulse wave velocity (PWV), a measure of the stiffness of the large arteries and an emerging parameter used as indicator of clinical cardiovascular risk. The method is based on measurement of brachial blood pressure during supra-systolic pressure inflation of a simple brachial cuff (the device is known as the Arteriograph (Tensiomed, Budapest, Hungary)). This occlusion yields pronounced first and secondary peaks in the pressure waveform, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 21 publications
(15 reference statements)
3
54
0
2
Order By: Relevance
“…In our study, aortic PWV was estimated from a single-site determination of the suprasystolic waveform. Although the principal underlying aortic PWV determination with Arteriograph has been called into question in a computer model [60], clinical data from an invasive study support the good agreement of aortic PWV as estimated by Arteriograph with direct intra-arterial measurement [39]. Any potential lack of precision of Arteriograph in estimating aortic PWV is expected to result in an underestimation of the genetic components of aortic PWV.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, aortic PWV was estimated from a single-site determination of the suprasystolic waveform. Although the principal underlying aortic PWV determination with Arteriograph has been called into question in a computer model [60], clinical data from an invasive study support the good agreement of aortic PWV as estimated by Arteriograph with direct intra-arterial measurement [39]. Any potential lack of precision of Arteriograph in estimating aortic PWV is expected to result in an underestimation of the genetic components of aortic PWV.…”
Section: Discussionmentioning
confidence: 95%
“…One year earlier Westerhof et al [5] in a more general paper already warned the scientific community that accurate location of reflection sites within the arterial tree would be elusive and that it is questionable that there would be one single location that generates the majority of reflections. The group of Segers et al [6] very recently refined their analyses, suggested alternative explanations and even questioned the working principle of the Arteriograph based on theoretical computer model simulations. Using more in-depth wave intensity analysis, they suggested that it is more likely that the second systolic peak of the Arteriograph is the forward compression wave caused by a re-re-re-reflection of the first incidence wave, thus an alternative explanation would be a wave that is travelling back and forth several times between the occlusion at the brachial cuff and a branching point between the brachial artery and the aorta (in the subclavian-axillary region?).…”
Section: Introductionmentioning
confidence: 97%
“…Thus, the Arteriograph essentially would pick up wave reflection phenomena confined to the stiffness of the brachial artery (axillobrachial stiffness). Trachet et al [6] further hypothesized that the good correlation of the PWV of the Arteriograph with established techniques might be owing to an intrinsic good correlation between brachial and central aortic stiffness. No doubt these suggestions are, in their turn, highly speculative and there is no need to emphasize that these data are model simulations and have not been validated against in-vivo catheterization data.…”
Section: Introductionmentioning
confidence: 98%
“…The authors may, however, have missed our follow-up study [3] in which we used the same model to demonstrate that the aforementioned correlation between Arteriograph and true aortic PWV is driven by changes in brachial artery stiffness. Changing the stiffness of all non-brachial arterial model segments did not affect the time interval between early and late systolic peaks in any way, whereas changing only brachial artery stiffness did have a significant effect (while aortic properties had remained the same).…”
mentioning
confidence: 99%